Cross-Cultural Validation and Reliability of the Schein’s Career Anchors Scale for Nurses - Asghari, Elnaz; Sarbakhsh, Parvin; Sheikhalipour, Zahra; Talebi, Rogayeh; Saberi Kajabadi, Amir (Advances in Nursing & Midwifery, 2024)
Introduction: The concept of career anchors pertains to identifying an individual's values, capabilities, interests, motivations, and needs concerning their professional trajectory. Career satisfaction and performance may be enhanced by tailoring career anchors to align with an employee's specific role. Nonetheless, there exists a paucity of studies investigating the psychometric properties of this scale within the nursing context. The present study has been conducted to address this gap. Methods: This research involved scaling tests administered to a substantial cohort of nurses (N=470) from university hospitals in East Azerbaijan Province, Iran, in December 2021. After translating the scale, experts assessed its content validity index and ratio. Both participants and specialists evaluated face validity. Confirmatory factor analysis was employed to ascertain convergent and discriminant validity. Additionally, the maximum shared squared variance, average shared squared variance, and construct reliability were calculated using the average variance extracted. The underlying structure of the scale was assessed via exploratory factor analysis, while internal consistency was determined using Cronbach’s alpha coefficient in SPSS Version 21. Results: The instrument's content was deemed adequate, reflecting high internal consistency and reliability. However, confirmatory factor analysis did not substantiate the existence of eight instrumental factors, while exploratory factor analysis revealed six product factors, which accounted for 62.626% of the total variance. Conclusions: The findings of this study indicate that Schein’s career anchors scale necessitates modification to be effectively utilized for identifying the predominant career anchors of nursing professionals. Recommendations have been provided for nurses on how to adapt and implement the scale appropriately.